The Islamic Method in the Qur’an: Keeping Life in Equilibrium - Aldi, Muhammad; Nur Wahyuni, Esa (Journal of English Language and Education, 2025)
The Qur'an as a guide to life for Muslims contains various methods in maintaining the balance of life, both in spiritual, social and moral aspects. This research examines the Islamic methods contained in the Qur'an in shaping the balance of life through an educational approach and moral development. Using conceptual analysis and a qualitative approach, this study identifies several main methods taught in the Qur'an, namely modeling, reward and punishment, reflection, experiential learning, and trial and error equilibrium. The results show that these methods not only shape individual character but also create harmony in social and spiritual life. The implications of this research contribute to the development of Islamic values-based educational strategies that can be applied in various contexts, including formal and non-formal education.